HUBUNGAN DURASI TIDUR DAN PERILAKU SEDENTARY DENGAN KEJADIAN OBESITAS PADA ANAK USIA SEKOLAH: Studi Literatur - Nessa Ishmah Munyati (2020)
Obesity is a situation where the accumulation of excess body fat can be a risk factor for comorbidity if left unchecked. Currently the incidence of obesity in children has become a quite serious challenge. Factors that cause obesity in children are due to lifestyle changes from traditional lifestyles to modern lifestyles or sedentary behavior. Another factor is the sleep duration, that short sleep duration in children makes children easily tired and causes children to be reluctant to physical activity at school. The purpose of this literature review is to find out whether there is a significant relationship between sleep duration, sedentary behaviour with incidence of obesity in school-age children. Literature reviews were obtained from databases (Pubmed, NCBI, Science Direct, and Google Scholar) the publication year of the journals is less than 5 years. The search terms included in the keywords are "obesity", "school-age children", "sedentary", and "sleep duration". The search results obtained 255 studies which were then filtered using the PICO method and the CRAAP method. After the studies were filtered the final result were 30 studies that will be reviewed. Short sleep duration in children due to sleep disorders, stay late at nightthe night and lifestyle of parents accompanied by spending time in sedentary behavior and spending less physical activity was a significant factor in the incidence of obesity in school age children